Group Guidance on the Integration of Islamic Values to Increase Student Communication Interactions - Fitra Herlinda; Andi Murniati; Nurhasnawati Nurhasnawati; Anisa Siti Nurjanah (STAI Hubbulwathan Duri, 2023)
Islamic values must be taught to pupils in order to help them develop strong moral character when dealing with others. Group direction can be used as one strategy to enhance student connection and communication. The aim of the study was to examine the effectiveness of value integration-based learning on student communication interactions. The type of research used is pre-experimental. The sample size is 21 students. The sampling technique used was purposive sampling. The observations showed an increase in student communication interactions in a conducive and Islamic direction, meaning that group guidance based on the integration of Islamic values was